Gene therapies for osteoarthritis: progress and prospects - Anais Defois; Nina Bon; Mathieu Mével; David Deniaud; Yves Maugars; Jérôme Guicheux; Oumeya Adjali; Claire Vinatier (Elsevier, 2024)
Introduction: Osteoarthritis (OA), the most common form of joint disease, affects more than 500 million people worldwide. This painful and debilitating disease imposes a huge socioeconomic cost worldwide. Despite years of promising research, no etiological drug has been successfully introduced into daily clinical practice. In this context, gene therapy (GT) is emerging as a tool capable of meeting an increasingly specialized medical need. Five GT drugs for OA are currently under clinical evaluation, demonstrating the relevance of this tool. However, the widespread use of GT is still limited by considerations of safety, long-term efficacy, controlled and specific targeting, and the presence of neutralizing immune responses. Cartilage, a tissue of interest to target in OA, is a complex tissue to penetrates with the various GT vectors. Methods: This manuscript reviews current clinical trials involving DNA-based GT for OA and suggests ways to improve recombinant adenoviral and adeno-associated viral vectors, including capsid engineering and transgene sequence optimization to achieve long-term expression of a given transgene exclusively in the target joint tissue, including cartilage. Results: This review then highlights that the use of hybrid serotypes and/or chemical modifications of capsids are promising for improved tissue targeting. In addition, the choice of promoter and type of vectorized nucleic acid (single- or double-stranded DNA) appears to be critical for efficient transgene expression. Conclusion: Finally, the combination of increasing knowledge about biocompatible materials and viral vectors should also be a way to improve transduction efficiency, increase the stability of transgene expression, and allow escape from neutralizing antibodies.